Income Inequality in Nepal - Kamal Raj Dhungel (Law and Economy, 2022)
Income inequality refers to a situation in which most of the national income is being distributed unevenly. Nepal is a small country with a population of nearly 30 million. It consists of a diverse society with disparity in health, education, opportunities, and income. The disparity in income distribution is measured with the help of Gini Coefficient with value ranges from zero (absolute equality) to 1 (absolute inequality). Presently the Gini coefficient of Nepal is 0.4. It indicates a big inequality in the distribution of the national income pie of Nepal in which a small portion of the population say the upper 10 percent are getting a big chunk of national income.